Educational software design: applying models of learning - Stephen Richards (Association for Learning Technology, 1996)
The model of learning adopted within this paper is the 'spreading ripples' (SR) model proposed by Race (1994). This model was chosen for two important reasons. First, it makes use of accessible ideas and language, .and is therefore simple. Second, .Race suggests that the model can be used in the design, of educational and training programmes (and can thereby be applied to the design of computer-based learning materials).